40th Fluid Dynamics Conference and Exhibit 2010
DOI: 10.2514/6.2010-4985
|View full text |Cite
|
Sign up to set email alerts
|

HIFiRE-5 Flight Vehicle Design

Abstract: The Hypersonic International Flight Research Experimentation (HIFiRE) program is a hypersonic flight test program executed by the Air Force Research Laboratories (AFRL)and Australian Defence Science and Technology Organization (DSTO). HIFiRE flight 5 is devoted to measuring transition on a three-dimensional body. This paper summarizes payload configuration, trajectory, vehicle stability limits and roughness tolerances. Results show that the proposed configuration is suitable for testing transition on a three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…During descent, latest (highest Reynolds number) leading edge transition occurred when the diameter Reynolds number at the most upstream joint was 1. The minor axis (centerline) transitioned at a lower Reynolds number than the leading edge, which is consistent with prior CFD 69,70 and wind tunnel measurements 53,65 at hypersonic conditions that indicated that the centerline is more unstable and prone to lower Reynolds number transition. Centerline transition also showed a more gradual progression over time than the leading edge transition.…”
Section: Transition Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…During descent, latest (highest Reynolds number) leading edge transition occurred when the diameter Reynolds number at the most upstream joint was 1. The minor axis (centerline) transitioned at a lower Reynolds number than the leading edge, which is consistent with prior CFD 69,70 and wind tunnel measurements 53,65 at hypersonic conditions that indicated that the centerline is more unstable and prone to lower Reynolds number transition. Centerline transition also showed a more gradual progression over time than the leading edge transition.…”
Section: Transition Resultssupporting
confidence: 76%
“…53 During ascent, earliest (highest Reynolds number) leading edge transition occurred when Re D reached 2.1x10 5 at the most upstream (nosetip/isolator) joint. During descent, latest (highest Reynolds number) leading edge transition occurred when the diameter Reynolds number at the most upstream joint was 1.…”
Section: Transition Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The descent phase exhibited significant deviations from the design trajectory, resulting in transition under angles of attack that were comparable to or even larger than the cone half-angle of 7 degrees. Thus, while flow conditions in the ascending phase of the HIFiRE-1 flight led to transition due to second-mode instability at sufficiently high values of the flight Mach number, both second mode and crossflow instabilities may be relevant to the transition process during the descending phase, in a way, similar to the transition mechanisms that are expected on the elliptic cone configuration from the HIFiRE-5 flight experiment 7,8 . Selected results pertaining to both second mode and crossflow instability over the HIFiRE-1 configuration are presented in sections 2 and 3, respectively.…”
Section: Introductionmentioning
confidence: 80%